Seaside Building Design: Principles and Practice Buildings in Maritime Zones (Innovative Renewable Energy,, 2018)
This one of a kind reference gathers numerous new studies examining the design of buildings in seaside locations. Chapters discuss design for various locations and seaside climates and include information regarding climate, materials, concepts of cooling and heating, vegetation and micro-climate, and weather conditions and sustainability. This book provides architects, engineers, builders, and students with design examples and applications that will enable them to design and build comfortable, cost-effective and sustainable buildings in maritime zones.